Islamization of Knowledge or Modern Myth ? Kantian Reflections on al-Faruqi’s Vision - Mohamad Topan; Rr.S Murtiningsih; A.H Utomo (Jaqfi: Jurnal Aqidah dan Filsafat Islam, 2025)
The concept of Islamization of knowledge according to Ismail Raji al-Faruqi using the perspective of Immanuel Kant's criticism. Al-Faruqi is a figure who plays an important role in introducing the idea of ​​Islamization of knowledge, an effort to reconstruct and reinterpret scientific disciplines based on Islamic principles. This article is a library research with a qualitative approach, descriptive critical analysis related to al-Faruqi concept of the Islamization of knowledge analyzed through Immanuel Kant's critical approach, especially related to rationality, ethics, and intellectual freedom. This analysis aims to see how these two thoughts can complement each other or even clash in an effort to combine religion and science. Kant's critical analysis of the concept of the Islamization of knowledge initiated by al-Faruqi contains problematic elements, especially in the metaphysical aspect, namely the concept of tawhid which is al-Faruqi theological idea when applied in the realm of science which should be empirical. On the other hand, there are important similarities between al-Faruqi and Immanuel Kant that science cannot be separated from morality which plays a role in directing science to contribute to the good of humanity.